2016
DOI: 10.1111/jocs.12739
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring Using Motor and Somatosensory Evoked Potentials in Aortic Surgery

Abstract: (1) Preservation of signals or return of signals is an excellent prognostic indicator for spinal cord function. (2) Intraoperative modifications in direct response to the signal change may have averted permanent paralysis in the patients with signal loss without neurologic injury. We have found MEP and SSEP neuromonitoring to be instrumental in the prevention of paraplegia. doi: 10.1111/jocs.12739 (J Card Surg 2016;31:383-389).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…117 Both MEP and the less well investigated SSEP neuromonitoring have been found useful in the prevention and prediction of paraplegia. 118,119 In a retrospective analysis, MEP was found useful in simultaneous arch and TA aortic surgery as part of a protocolized brain and spinal cord protection bundle. 120 The selective use of MEP and SSEP monitoring in aortic arch surgical or endovascular repair may therefore be considered based on the requirements of the individual patient, surgery or procedure, on the urgency of the procedure and on institutional resources.…”
Section: Central Nervous System Electrophysiological Function Monitoringmentioning
confidence: 99%
“…117 Both MEP and the less well investigated SSEP neuromonitoring have been found useful in the prevention and prediction of paraplegia. 118,119 In a retrospective analysis, MEP was found useful in simultaneous arch and TA aortic surgery as part of a protocolized brain and spinal cord protection bundle. 120 The selective use of MEP and SSEP monitoring in aortic arch surgical or endovascular repair may therefore be considered based on the requirements of the individual patient, surgery or procedure, on the urgency of the procedure and on institutional resources.…”
Section: Central Nervous System Electrophysiological Function Monitoringmentioning
confidence: 99%
“…The relationship between changes in MEP at an early reversible stage and the pathological damage of anterior horn motor neurons was also investigated. Previous studies have demonstrated that MEPs are highly sensitive to SCI when recorded from muscles in the lower extremities ( 35 , 36 ). A study by de Haan et al ( 15 ) demonstrated that myogenic responses disappeared within 2 min after the initiation of arterial occlusion in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 3 decades, various intraoperative strategies have been applied to protect the spinal cord and prevent such paraplegia with various levels of success, including left heart bypass, epidural cooling, 1 motor evoked potential monitoring, 2 and preoperative computed tomography (CT) angiography (CTA) and magnetic resonance angiography (MRA) to identify and preserve the artery of Adamkiewicz 3 and provide cerebrospinal fluid (CSF) drainage. 4,5 There is currently a class IB recommendation for CSF drainage for patients at high risk of SCI undergoing open DTAA or TAAA repair, according to the American College of Cardiology Foundation and American Heart Association guidelines, 6 and a class IB recommendation for CSF drain (CSFD) use in all patients according to the European Association for Cardiothoracic Surgery guidelines.…”
Section: Video Clip Is Available Onlinementioning
confidence: 99%
“…Over the past 3 decades, various intraoperative strategies have been applied to protect the spinal cord and prevent such paraplegia with various levels of success, including left heart bypass, epidural cooling, 1 motor evoked potential monitoring, 2 and preoperative computed tomography (CT) angiography (CTA) and magnetic resonance angiography (MRA) to identify and preserve the artery of Adamkiewicz 3 and provide cerebrospinal fluid (CSF) drainage. 4 , 5 …”
mentioning
confidence: 99%